Analisis Perceraian Akibat Kekerasan Dalaam Rumah Tangga di Pengadilan Agama Purwokerto (Studi Putusan Pengadilan Nomor 1022/Pdt.G/2021/PA.Pwt) - Toriq Fernanda, Rio Daniel; Hidayah, Astika Nurul (JURNAL PENELITIAN SERAMBI HUKUM, 2024)
Divorce is one of the undesirable things for both husband and wife in a marriage. One of the factors that often triggers divorce is Domestic Violence. In the Decision of the Purwokerto Religious Court Number 1022/Pdt.G/2021/PA.Pwt, the panel of judges granted the Plaintiff's lawsuit. This study aims to determine the elements of Domestic Violence that lead to divorce as a result of Domestic Violence. This research uses a normative juridical method with a statutory approach, case approach, and conceptual approach. Data were obtained from literature study. The data were analyzed using descriptive analysis method. Based on the analysis, it was found that in the Decision of the Purwokerto Religious Court Number 1022/Pdt.G/2021/PA.Pwt, Domestic Violence occurred twice, and the Defendant left the wife after the dispute for 9 months until the case was filed, which was sufficient grounds for divorce. In the case of the Decision of the Purwokerto Religious Court Number 1022/Pdt.G/2021/PA.Pwt, the granting of the divorce lawsuit filed by the Plaintiff has provided legal certainty.